2021
DOI: 10.1111/jir.12804
|View full text |Cite
|
Sign up to set email alerts
|

Medical conditions of children and young people with Down syndrome

Abstract: AbtractBackgroundThe life expectancy of people with Down syndrome (DS) has significantly increased in the last decades. We describe the congenital malformations and main comorbidities of a cohort of children and young people with DS and analyse their differences according to age and gender groups.MethodsThis retrospective cross‐sectional study was conducted at DS centre of Bambino Gesù Children's Hospital in Rome (Italy). The period for reviewing all electronic health records ran from July 2016 to September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…Consistent with prior reports (e.g. Alexander et al 2016;Valentini et al 2021;Baksh et al 2023; see also Bull et al 2022), individuals with DS were found to exhibit high prevalence of a range of health conditions, including circulatory complications, digestive and gastrointestinal issues, metabolic and endocrine issues, sensory difficulties (vision and hearing), mental and neurological concerns and others. For our sample, circulatory conditions were particularly found as highly prevalent among DS cases, as differences in heart formation at birth among many individuals with DS have been linked to various cardiac complications, including heart failure, (pulmonary) hypertension and atrioventricular block, aside from CHD (Bush et al 2018).…”
Section: Co-occurring Health Conditions In Down Syndromesupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with prior reports (e.g. Alexander et al 2016;Valentini et al 2021;Baksh et al 2023; see also Bull et al 2022), individuals with DS were found to exhibit high prevalence of a range of health conditions, including circulatory complications, digestive and gastrointestinal issues, metabolic and endocrine issues, sensory difficulties (vision and hearing), mental and neurological concerns and others. For our sample, circulatory conditions were particularly found as highly prevalent among DS cases, as differences in heart formation at birth among many individuals with DS have been linked to various cardiac complications, including heart failure, (pulmonary) hypertension and atrioventricular block, aside from CHD (Bush et al 2018).…”
Section: Co-occurring Health Conditions In Down Syndromesupporting
confidence: 87%
“…2021; Valentini et al . 2021). Unique to our current study is that these health conditions remain prevalent in DS cases even when compared with other IDDs, highlighting their distinct or specific clinical features (Results S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DS is associated with increased risk of several medical issues, such as congenital heart disease, obstructive sleep apnoea, celiac disease, and endocrine abnormalities, including thyroid dysfunctions ( Antonarakis et al, 2020 ). Individuals with DS exhibit a range of thyroid dysfunctions that encompass congenital hypothyroidism, subclinical hypothyroidism (SH), acquired hypothyroidism (autoimmune/non autoimmune), and hyperthyroidism ( Pierce et al, 2017 ; Valentini et al, 2021 ). For example, higher rates of hypothyroidism have been documented, with estimated prevalence of 23.5% in pediatric age and 39–61% in adult age ( Carroll et al, 2008 ; Tsou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a well-established association between Down syndrome (DS) and the development of moyamoya syndrome (MMS) (7,15,16) with particularly high rates in children (17). Higher rates of both autoimmune disease and thyroid autoantibodies in this population raise additional concerns that these factors may yield a greater risk of the development of MMS although this has never been studied (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%